Synthesis and modelling of radio frequency integrated planar spiral inductor [compact dics] - 188853 See, Guan Huei (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004